Responses of the five shallot cultivars to salicylic acid treatment under stress drought conditions - Khotimah, Khusnul; Randi, Mohammad Jusuf; Juwanda, Muhammad; Laela, Titin Nur (Jurnal Ilmu Pertanian, 2024)
Salicylic acid is a growth hormone that has been widely used to induce resistance to biotic and abiotic stresses. Plant genotypes have different responses to drought stress conditions. This study aimed to analyze the response of five shallot cultivars to drought stress mediated by salicylic acid. A total of five shallot cultivars treated with salicylic acid were tested under drought stress conditions. This study used a completely randomized design with 3 factors, namely the first was the concentration of salicylic acid (0 mM, 0.5 mM, and 1 mM), the second was the shallot cultivar (Bima Brebes, Tajuk, Bauci, Super Philip and Bima Juna), and the third was drought stress (without drought stress and with drought stress). All collected data were subjected to analysis of variance (ANOVA) and the mean differences were compared using Duncan Multiple Range test (α = 95%). Observation variables included leaf length, leaf number, stomatal density, relative water content, total chlorophyll, and leaf proline content. Based on the results of the study, drought stress significantly decreased leaf length and leaf number, reduced chlorophyll content, relative water content and stomatal density, chlorophyll content, and increased proline content of the leaves. On the other hand, exogenous application of SA to drought stressed shallot plants improved morphophysiological characters of shallot. Application of 1 mM salicylic acid was the best concentration. The results of this study also obtained two cultivars that showed fairly consistent morphophysiological performance, namely Bima Juna and Tajuk cultivars. These two cultivars can be recommended as genetic materials in the assembly of drought-tolerant varieties mediated by salicylic acid.